Decomposer community in boreal coniferous forest soil after forest harvesting : mechanisms behind responses - Siira-Pietikäinen, Anne (2002)
Effects of different forest regeneration methods on decomposer animals in boreal coniferous forest and the mechanisms behind the responses were studied in three field experiments and a laboratory experiment. The study focused mainly on enchytraeids, collembolans and microbes. In addition, decomposition, soil nitrogen availability and primary production were measured. In the first experiment, treatments with untreated controls were selection felling, gap felling with and without harrowing, retention felling (tree patches retained) and clear felling. The other field experiments were established in untreated forest to exclude major effects of changes in microclimate. The studied factors were exclusion of mycorrhizal connections (trenching), exposure of mineral soil (sod cutting) and addition of felling residues. The functional role of enchytraeids in different soil layers was studied in the laboratory experiment. Clear felling decreased fungal biomass and increased enchytraeid numbers. Microbial respiration decreased and community structure of microbes (PLFA pattern) changed as compared with the control. In addition, some litter dwelling macroarhropods (certain beetle species, spiders, scale insects) decreased in numbers. Responses in small gaps were similar to those in clear fellings, but smaller, whereas selection felling had no influence on the studied organisms. Trenching and sod cutting induced similar changes to measured variables as observed in clear fellings. Felling residues (slash) had no effect on soil organisms. Effects of enchytraeids on nitrogen mineralisation were dependent on soil layer and resource quality. It was concluded that despite some responses, the decomposer community is well buffered against initial changes caused by forest harvesting.